ANALYSIS OF THE FUCTIONAL ROLE OF RICE MILLING COMPANY ON THE WELFARE OF RICE FARMERS IN THE SUB-DISTRICT BUAY MADANG TIMUR DISTRICT OKU TIMUR - Aisah Aisah (Jurnal AKTUAL, 2018)
Rice Milling Company is rice industry’s oldest and largest classified in Indonesia, which is able to absorb more than 10 million workers, handles more than 40 million tons of grain.  Rice Milling Company agro-industy is the central point, because this is where the main product is obtained in the form of rice and raw materials for advanced processing of food and industrial products.  Rice Miling Unit in the district of OKU Timur there is some skala, ranging form small-scale, medium-scale to large-scale.  Fuctional benefits of each different scale milling is also different.  The average rice farmers often sell gabahnya to the rice milling unit closest to the place residence, whether it is large-scale, medium and small.  Rice produced by the milling-grinding different quality.  Usually when a large-scale millimg yield of rice is cleaner than the other scale.  But it does not become a reference for milling grain milling usually depends on consumer demand.  The purpose of the study are : 1.  To determine levels of volume (tonnage) and the retention time of each service fuctional rice storage (barns) wich carried a different scale rice milling unit.  2.  To determine differences in the bebefits of economic transactions received by farmers and rice millers of different scale of business, especially when seen from the level of the milling costs, the purchase price of rice by rice milling unit, and the quality of milling services and service scale.  The result show that : the fuctional role of each is different milling.  Large-scale milling has three fuctional roles are : Processing, storage and distribution.  Medium-scale miling functional has two roles, namely : processing and distribution.  While small-scale rice milling unit has only two functional roles are : processing and storage.